Comparison of Transfer Learning Using VGG16, MobileNetV2, and ResNet50 for Pornography Image Detection - SihWardana, Christopher Ade; Isa, Sani Muhamad (International Journal of Advances in Data and Information Systems, 2025)
The rapid growth of digital technology is vital for the Indonesian Scout to reach and interact with its members. The National Indonesian Scout (Kwarnas) uses the “Ayo Pramuka” social media application to support this. However, such platforms risk exposing users, especially teenagers, to harmful content like pornography. This research applies Computer Vision and Transfer Learning Convolutional Neural Networks (CNNs) to detect pornographic images automatically. The objective is to identify the CNN model (VGG16, MobileNet V2, ResNet 50) with the highest detection accuracy and determine the impact of color space preprocessing. The method includes two stages first, image preprocessing by converting RGB images to HSV and YCbCr second, feature extraction using pre-trained CNNs with freezing and fine-tuning. A dataset of 4060 images was used for training and testing. Without preprocessing, VGG16 achieved the best accuracy of 99.01%. When RGB images were converted to HSV, ResNet 50 produced the highest accuracy of 99.51%. The findings show that combining color space transformation and Transfer Learning CNN significantly improves pornographic content detection in the “Ayo Pramuka” Application, enhancing safe digital engagement for Indonesian Scouts.